Long Noncoding RNA LOC100129940-N Is Upregulated in Papillary Thyroid Cancer and Promotes the Invasion and Progression. (7th April 2019) - Choy, Manting; Guo, Yan; Li, Hai; Wei, Guohong; Ye, Runyi; Liang, Weiwei; Xiao, Haipeng; Li, Yanbing; Guan, Hongyu
Abstract : Thyroid cancer is the most common endocrine malignancy, and its incidence has increased rapidly in recent decades worldwide. Papillary thyroid cancer (PTC) is the most common type of all thyroid cancers. The molecular mechanisms underlying the disease still need to be further investigated. Long noncoding RNAs (lncRNAs), a class of noncoding RNAs (ncRNAs) longer than 200 nucleotides, are aberrantly expressed in malignant diseases, including PTC. Here, we identified a novel isoform of LOC100129940 and designated it as LOC100129940-N. We demonstrated that the expression level of LOC100129940-N was elevated in PTC, indicating that LOC100129940-N may be involved in PTC development and progression. Moreover, our results showed that overexpression of LOC100129940-N promoted, whereas silencing of LOC100129940-N suppressed, PTC cell proliferation, invasion, and migration. Mechanistically, LOC100129940-N played an important role in activating Wnt/ β -catenin signaling and upregulating downstream target genes. Taken together, we demonstrate that LOC100129940-N promotes the activation of Wnt/ β -catenin signaling, which in turn regulates the downstream target genes, thereby enhancing invasion and progression of PTC.